2016
DOI: 10.11646/zootaxa.4196.2.8
|View full text |Cite
|
Sign up to set email alerts
|

A new cave-dwelling species of the genus Mesoiulus Berlese, 1886 (Diplopoda, Julida, Julidae) from Turkey

Abstract: A new cave-dwelling species of the poorly defined genus Mesoiulus Berlese, 1886, M. taurus sp. nov., is described from the Zindan Cave, Isparta, Western Taurides, Turkey. A brief discussion of the relationship between M. taurus sp. nov. and the most similar species (M. ciliciensis Strasser, 1975) is presented, as well as a map showing the distribution of the genus Mesoiulus in Turkey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 738 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In studies conducted in Turkish caves, more than 200 invertebrates have been identified, 105 of which are endemic to Anatolia. More than 80% of the identified species were Arthropoda (Kunt et al, 2010;Antić et al, 2016). The reason for high endemism of the species living in the caves is that these species adapt to separated subterranean environments (Armas & Alayon Garcia, 1984;Juberthie & Decu, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…In studies conducted in Turkish caves, more than 200 invertebrates have been identified, 105 of which are endemic to Anatolia. More than 80% of the identified species were Arthropoda (Kunt et al, 2010;Antić et al, 2016). The reason for high endemism of the species living in the caves is that these species adapt to separated subterranean environments (Armas & Alayon Garcia, 1984;Juberthie & Decu, 1994).…”
Section: Introductionmentioning
confidence: 99%